Study of Potential and Strategy for Sustainable Tourism Development in the Semanting Bay Mangrove Ecotourism Conservation Area, Berau Regency - Susanti, Endah (Gorontalo Development Review, 2025)
This study examines the potential, practices, and strategies for sustainable tourism development in the Semanting Bay Mangrove Ecotourism, Berau Regency. The background of the study departs from the role of tourism as an economic driver that must maintain the ecological carrying capacity and local socio-cultural values. The study uses a qualitative descriptive approach in a natural setting with primary (in-depth interviews/observation) and secondary (policy documents) data sources, purposive selection of informants (village governments, ecotourism managers, and Pokdarwis), and Miles–Huberman analysis (reduction, presentation, drawing conclusions) accompanied by triangulation of sources and methods. The results show that Teluk Semanting has strong prospects as an ecotourism destination: the mangrove ecosystem ±741 ha and the existence of proboscis monkeys is the main capital; sustainability practices have been carried out through destination levies, MSME promotion events, waste management, environmental education, and conservation—but the degree is not optimal. Challenges include limited basic infrastructure (access to roads, clean water, toilets, internet networks), effectiveness of promotions, and strengthening the participation and capacity of local human resources. Priority strategies include structured multi-stakeholder collaboration, improving the quality of "green" tourism products and experiences, strengthening tourist literacy, and regular coordination forums across government units. This study recommends strengthening community capacity and participatory governance so that economic, social, and environmental benefits are distributed fairly and sustainably across generations.